Review on the use of piezoelectric materials for active vibration, noise, and flow control - Shivashankar, P; Gopalakrishnan, S (Smart materials and structures, 2020)
Considering the number of applications, and the quantity of research conducted over the past few decades, it would not be an overstatement to label the piezoelectric materials as the cream of the crop of the smart materials. Among the various smart materials, the piezoelectric materials have emerged as the most researched material for practical applications. They owe it to a few key factors like low cost, large frequency bandwidth of operation, availability in many forms, and the simplicity offered in handling and implementation. For piezoelectric materials, from an application standpoint, the area of active control of vibration, noise, and flow, stands, alongside energy harvesting, as the most researched field. Over the past three decades, several authors have used piezoelectric materials as sensors and actuators, to (i) actively control structural vibrations, noise and aeroelastic flutter, (ii) actively reduce buffeting, and (iii) regulate the separation of flows. These studies are spread over several engineering disciplines-starting from large space structures, to civil structures, to helicopters and airplanes, to computer hard disk drives. This review is an attempt to concise the progress made in all these fields by exclusively highlighting the application of the piezoelectric material. The research carried out in the past five years, in the areas of modeling, and optimal positioning of piezoelectric actuators/sensors, for active vibration control (AVC), are covered. Along with this, investigations into different control algorithms, for the piezoelectric based AVC, are also reviewed. Studies reporting the use of piezoelectric modal filtering and self sensing actuators, for AVC, are also surveyed. Additionally, research on semi-AVC techniques like the synchronized switched damping (on elements like resistor, inductor, voltage source, negative capacitor) has also been covered.